A New Monoclonal Antibody, mAb 4A12, Identifies a Role for the Glycosaminoglycan (GAG) Binding Domain of RANTES in the Antiviral Effect against HIV-1 and Intracellular Ca(2+) Signaling - Burns, Jennifer M. (The Rockefeller University Press, 1998)
The β-chemokine RANTES (regulated on activation, normal T cell expressed and secreted) suppresses the infection of susceptible host cells by macrophage tropic strains of HIV-1. This effect is attributed to interactions of this chemokine with a 7-transmembrane domain receptor, CCR5, that is required for virus–cell fusion and entry. Here we identify domains of RANTES that contribute to its biological activities through structure–function studies using a new monoclonal antibody, mAb 4A12, isolated from mice immunized with recombinant human RANTES. This monoclonal antibody (mAb) blocked the antiviral activity of RANTES in infectivity assays with HIV-1(Bal), and inhibited the mobilization of intracellular Ca(2+) elicited by RANTES, yet recognized this chemokine bound to cell surfaces. Epitope mapping using limited proteolysis, reversed phase high-performance liquid chromatography, and mass spectrometry suggest that residues 55–66 of RANTES, which include the COOH-terminal α-helical region implicated as the glycosaminoglycan (GAG) binding domain, overlap the determinant recognized by mAb 4A12. This is supported by affinity chromatography studies, which showed that RANTES could be eluted specifically by heparin from a mAb 4A12 immunoaffinity matrix. Removal of cell surface GAGs by enzymatic digestion greatly reduced the ability of mAb 4A12 to detect RANTES passively bound on cell surfaces and abrogated the ability of RANTES to elicit an intracellular Ca(2+) signal. Taken together, these studies demonstrate that the COOH-terminal α-helical region of RANTES plays a key role in GAG-binding, antiviral activity, and intracellular Ca(2+) signaling and support a model in which GAGs play a key role in the biological activities of this chemokine.